Strategi Bertahan Hidup Pedagang Kaki Lima di Tengah Pandemi Covid-19 - Irawan, Bagus Fajar; Fauzi, Agung (Lembaga Yasin AlSys, 2022)
The Covid-19 pandemic that came so suddenly had a fairly large economic downturn. None of us can predict how long this pandemic will last, including the impacts that come with it. Therefore, flexibility for business actors, including changing the business plans that were made in the days before the pandemic occurred, is very necessary if they want to maintain their business. The strategy of street vendors (PKL) who sell in Tangerang Regency is to find out what obstacles are faced by street vendors in Tangerang Regency. This research was conducted by field research and using a descriptive qualitative approach, namely interviews with street vendors. And the interviews conducted were relaxed, uncomplicated, and those proposed were not integrative but only to obtain the desired data. The results of this study are the obstacles faced by traders, namely and unofficial trading places.